Application of mesenchymal stem cell-derived exosomes from different sources in intervertebral disc degeneration - Xia, Yuanliang; Yang, Ruohan; Hou, Yulin; Wang, Hengyi; Li, Yuehong; Zhu, Jianshu; Fu, Changfeng (Frontiers in Bioengineering and Biotechnology, 2022)
Intervertebral disc degeneration (IVDD) is a main cause of lower back pain, leading to psychological and economic burdens to patients. Physical therapy only delays pain in patients but cannot eliminate the cause of IVDD. Surgery is required when the patient cannot tolerate pain or has severe neurological symptoms. Although surgical resection of IVD or decompression of the laminae eliminates the diseased segment, it damages adjacent normal IVD. There is also a risk of re-protrusion after IVD removal. Cell therapy has played a crucial role in the development of regenerative medicine. Cell transplantation promotes regeneration of degenerative tissue. However, owing to the lack of vascular structure in IVD, sufficient nutrients cannot be provided for transplanted mesenchymal stem cells (MSCs). In addition, dead cells release harmful substances that aggravate IVDD. Extracellular vesicles (EVs) have been extensively studied as an emerging therapeutic approach. EVs generated by paracrine MSCs retain the potential of MSCs and serve as carriers to deliver their contents to target cells to regulate target cell activity. Owing to their double-layered membrane structure, EVs have a low immunogenicity and no immune rejection. Therefore, EVs are considered an emerging therapeutic modality in IVDD. However, they are limited by mass production and low loading rates. In this review, the structure of IVD and advantages of EVs are introduced, and the application of MSC-EVs in IVDD is discussed. The current limitations of EVs and future applications are described.